Urban agriculture studies - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Fourteen scholarships are available for masters and PhD students on urban and peri-urban agriculture. They can be used for field research from 3 to 12 months, up to CAN $ 20,000. For 2002, apply before end-December 2001.Agropolis IDRCCP 8500,...